Technical and economic study of commercial varieties of green beans with plastic mulch (2023)
Green beans are consumed worldwide due to their healthy nutritional properties. These are an important part of the modern “Grab-and-Go” diet, along with the traditional diet. Green beans are rich in protein, vitamins, fiber, folic acid and numerous minerals. In Colombia, the production of green beans is concentrated in the eastern mountain range, where there are currently low yields due to the phytosanitary problems associated with the traditional Blue Lake variety, added to the little implementation of production strategies such as plastic mulches. Thus, four varieties of green beans with plastic mulch were technically and economically evaluated. The experimental design used was complete randomized blocks with eight treatments, resulted of factors combination of the varieties (UNAPAL Milenio, Blue Lake Pole, Blue Lake National and Blue Lake S-7) and with and without plastic mulch, with four repetitions and an experimental unit of 25 plants. Planting distances were 0.25 m between plants and 1.2 m between rows for a population density of 33,333 plants/ha. The variables evaluated were: yield components, production per plant (g) and crop yield (t ha-1). The plastic mulch (black-black) had no differential effect on the agronomic behavior of the green bean varieties in the study area. The UNAPAL Milenio variety, with 9,134 kg ha-1, reached an agronomic behavior similar to the conventional Blue Lake variety with 9,717 kg ha-1. The Blue Lake variety presented the best economic behavior with a cost-benefit ratio of 1.15 and a rate of return of 14.85%.